A Clinical Trial to Detect Subclinical Transfusion-Induced Lung Injury During Surgery. Issue 2 (April 2016) - Feiner, John R.; Gropper, Michael A.; Toy, Pearl; Lieberman, Jeremy; Twiford, Jenifer; Weiskopf, Richard B.
Abstract : Surv Anesthesiol 2016;60(2):76–77 Transfusion-related acute lung injury (TRALI) is defined as new acute lung injury (PaO2 /FIO ⩽ 300 mg) that develops during or within 6 hours of transfusion, with no temporal relation to an alternative risk factor for acute lung injury. It is 1 of the leading causes of transfusion-related mortality.